PERANCANGAN SISTEM MONITORING JARAK JAUH PINTU PINTAR RUMAH INDEKOS BERBASIS IOT (INTERNET OF THINGS) MENGGUNAKAN PLATFORM BLYNK - Leander, Daud Elia; Ashidiqie, Muhammad Fikry; Udoyono, Kodar (STMIK Subang, 2024)
Security systems are crucial for ensuring the safety of residents, particularly in boarding houses, which tend to be more vulnerable to criminal activities. In this study, a door security system based on the IoT (Internet of Things) was developed using the Blynk platform. The system is designed to allow boarding house owners and residents to monitor door access via a smartphone, enhancing security more effectively and efficiently. The system utilizes a NodeMCU microcontroller as the control center, which is connected to a door sensor, and provides real-time notifications through the Blynk application. Additionally, activity log features and remote control capabilities are integrated into the system. Testing was conducted through simulation scenarios to evaluate the system's response to various security conditions. The results showed that the system operates effectively and provides real-time notifications to users. This system is expected to serve as an alternative solution for improving boarding house security that is easy to implement and use.